Pengakuan, Pengukuran, Penyajian, dan Pengungkapan Biaya Limbah - Intan Diah Pratiwi; Yosefa Sayekti; Imam Mas'ud (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to determine the application of environmental accounting on the cost of waste at PT. Cement Puger Jaya Raya Sentosa. This research is qualitative using triangulation method. Resulth is accounting practices (the recognition, measurement, presentation and disclosure) the cost of waste carried out by PT. Cement Puger Jaya Raya Sentosa almost in accordance with the Framework for the Preparation and Presentation of Financial Statements (KDPPLK) however, PT. Cement Puger Jaya Raya Sentosa yet have a complete financial statement. The financial statements are owned by PT. Cement Puger Jaya Raya Sentosa until this research still consists of report production costs, fixed asset depreciation report, and income statement. Keywords: Accounting, Environmental, Waste, Cement Factory, Report